Ectopic thyroid in the anterior mediastinum - Guimarães, MJ (2011)
Ectopic thyroid is a rare condition, and its location in the anterior mediastinum is even rarer, there having been only 5 reported cases in the past 30 years. Here, we describe 2 clinical cases and present a review of the literature regarding the etiology, embryology and clinical manifestations of ectopic thyroid.